The Geographic Concentration of Industry: Does Natural Advantage Explain Agglomeration? - Ellison, Glenn; Glaeser, Edward L (American Economic Review, 1999)
The Geographic Concentration of Industry: Does Natural Advantage Explain Agglomeration? by Glenn Ellison and Edward L. Glaeser. Published in volume 89, issue 2, pages 311-316 of American Economic Review, May 1999